2018
DOI: 10.1002/jobm.201800212
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma mediate early and enhanced lignifications in chickpea during Fusarium oxysporum f. sp. ciceris infection

Abstract: Lignifications in secondary cell walls play a significant role in defense mechanisms of plants against the invading pathogens. In the present study, we investigated Trichoderma strain specific lignifications in chickpea plants pre‐treated with 10 potential Trichoderma strains and subsequently challenged with the wilt pathogen Fusarium oxysporum f. sp. ciceris (Foc). Trichoderma‐induced lignifications in chickpea were observed through histochemical staining and expression of some genes of the lignin biosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…leads into induction and accumulation of the PR proteins at early stages of root colonization (Yedidia et al, 2000). In many studies, it has been demonstrated that treatment of plants with beneficial microbes, particularly Trichoderma , enhances plant resistance against pathogens through ROS generation and lignification (Patel et al, 2017; Meshram et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…leads into induction and accumulation of the PR proteins at early stages of root colonization (Yedidia et al, 2000). In many studies, it has been demonstrated that treatment of plants with beneficial microbes, particularly Trichoderma , enhances plant resistance against pathogens through ROS generation and lignification (Patel et al, 2017; Meshram et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma spp. can produce hydrolytic enzymes, which play an important role in antagonism processes (Meshram et al., 2019). When Trichoderma detects a pathogen, it wraps it with its hyphae to subsequently produce cell wall‐degrading enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this endophytic fungus works as a symbiont, favoring plants' development and increasing their resistance to biotic and abiotic stress (Rebolledo‐Prudencio et al., 2020). It can activate the induced systemic resistance response, the accumulation of proteins, the generation of reactive oxygen species, the development of lignifications, and the production of phytoalexins (Meshram et al., 2019). Furthermore, it also contributes to plant growth by modulating phytohormones and solubilizing soil nutrients (Rebolledo‐Prudencio et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that lignin content and PPO activity were significantly correlated with the control effect of sulfur application on kiwifruit bacterial canker. Defensive-induced lignification is a conserved basic defense mechanism in plant immune response to a variety of pathogens [36,37]. It has been reported that many enzymes are involved in the biosynthesis of lignin [35,38].…”
Section: Discussionmentioning
confidence: 99%